Estimating Coastal Flood Hazard of Tossa de Mar, Spain: A Combined Model – Data Interviews Approach - Karas, C (Springer Science and Business Media B.V., 2021)
Human settlements in coastal areas are highly vulnerable to extreme events, especially in the Mediterranean area, which houses a large number of tourists during the summer and autumn months. It is important to carry out hazard studies at local scale to improve our understanding of natural and anthropogenic processes involved in episodes of coastal flooding. We reconstruct and characterize an extreme weather event in Tossa de Mar (northeastern Spain) and the subsequent urban flooding that occurred in 2008. Our results show flood heights up to 1.27 m, with the maximum occurring between 24 and 64 h after the start of the event. This is broadly consistent with the reconstructions obtained through interviews and photographs. Based on model simulations, we produce a hazard map for the town based on hydrodynamic scenarios for different return periods. We show that the southern part of the town is more susceptible to flooding, whereas the northern part is relatively resilient to extreme events. We recommend the adaption of a currently existing dune by adding vegetation and slightly increasing its height. This low economic cost action would significantly reduce flooding and increase resilience in this area. © 2021, The Author(s), under exclusive licence to Springer Nature B.V.